Utilization of dental radiology services during the COVID-19 pandemic and factors that influence it in Banda Aceh - Kemala HAYATI; Mira Zahratul RIAD; Munifah MUNIFAH (Dentistry Faculty, 2022)
The COVID-19 pandemic spread worldwide until it finally entered Indonesia in March 2020.Radiographic examination is used to make a diagnosis, make a treatment plan and evaluate optimal treatmentoutcomes. In March 2020, the Central Board of the Dental Medical Radiology Association (PPIRKG) appealed topostpone all radiological examinations except in emergency conditions. Still, the need for dental care continues toincrease. To determine the use of radiography services in dentistry during the COVID-19 pandemic and the factorsthat influence it in Banda Aceh. The total subjects in this study were 104 patients from the Dental Radiology sectionof RSGM FKG USK. Questionnaires were given through social media in the form of online questionnaires. Results:The results showed that the utilization of dental radiology at the RSGM FKG USK during the 2020-2021 COVID-19pandemic decreased. The utilization of dental radiology services at the RSGM during the COVID-19 pandemic hasreduced several factors. The number of patient visits to the radiology of the RSGM FKG USK has decreaseddramatically during 2020-2021. Most patients stated that they preferred to self-isolate at home and did not go to theRSGM during the COVID-19 pandemic. However, they thought radiology services at the RSGM during thepandemic were going well. KEYWORDS: Pandemic, COVID-19, Radiology, Dental Clinic